The Civilized Speech of a Storyteller through the Oral Narrative Awang Batil Performance [Pengucapan Beradab Penglipur Lara melalui Naratif Lisan Persembahan Awang Batil] - Rohayati Binti Junaidi (Tanjung Malim, 2024)
The Civilized Speech of a Storyteller through the Oral Narrative Awang Batil Performance [Pengucapan Beradab Penglipur Lara melalui Naratif Lisan Persembahan Awang Batil] by Rohayati Binti Junaidi